Institutional analysis of regionalism in Japan: a sociological case study from Owase, Japan. Issue 2 (2nd April 2020) - Kie, Sanada
Abstract: Since the end of 1990s, the Japanese government has made a clear neoliberal shift in its strategy for regional governance. Within the ongoing framework of regional revitalisation ( chihôsôsei ), various local attempts to foster revitalisation ( kasseika ) are underway. Two seemingly irreconcilable views prevail in connection with volunteer-based localism: local participation and the mobilisation of civic action. However, the ways in which these seemingly distinct phenomena can socially coexist are relatively unexplored. Against this background, this article aims to offer a critical re-examination of regional revitalisation projects in Japan and it focuses on the correlation between local participation patterns and local power structures. Taking one community as its empirical case study, the central question posed is: 'In reality, who are the motivated participants in the community-revitalisation project?' What becomes apparent is, on the one hand, the locality's power structure strongly limits the level of participation in the project; on the other hand, the locality's inhabitants experience the ongoing situation as fundamentally fair and reasonable. On this basis, this article argues that the state's governing discourse of neoliberalism is able to advance at the local level while simultaneously and unwittingly perpetuating the structure of social segregation.